Relationship between internet addiction and sleep quality in university students - Sağar, Mehmet Enes; Kök Eren, Hülya (Journal of Dependence, 2022)
Objective: The purpose of this study was to investigate the relationship between internet addiction and sleep quality in university students. Method: A total of 424 university students were included in the study. The study was conducted online due to the COVID-19 pandemic. “Personal Information Form”, “Young’s Internet Addiction Test-Short Form (YIAT-SF)”, and “Pittsburgh Sleep Quality Index (PSQI)” were used as data collection tools. Results: The average internet addiction scores of individuals with poor sleep quality were higher than the average internet addiction scores of individuals with good sleep quality. In addition, internet addiction significantly affected the sleep quality of university students. It has been determined that internet addiction is an important parameter affecting sleep quality, when internet addiction scores increase by 1 unit, the risk of poor sleep quality will increase by 8.7%. Conclusion: There is a significant relationship between internet addiction and sleep quality of university students and that internet addiction negatively affects sleep quality. In this context, it is expected that holistic studies to be carried out in terms of reducing internet addiction and increasing sleep quality of university students will shed light on both theoretical and applied studies.